2011
DOI: 10.1007/s00296-011-2251-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mean platelet volume in children with familial Mediterranean fever

Abstract: To evaluate the Mean Platelet Volume (MPV) levels in children diagnosed with familial Mediterranean fever (FMF), during attack and attack-free periods. The records of a total of 117 children with FMF, diagnosed using the Tel-Hashomer criteria, have been scanned. The study consisted of 53 patients during an attack (group 1), 64 patients in attack-free period (group 2), and 57 healthy controls (group 3). Erythrocyte sedimentation rate, C-reactive protein, white blood cell count, platelet count, and MPV levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 22 publications
5
19
0
5
Order By: Relevance
“…Usefulness of MPV in assessment of atherosclerotic risk in cases with FMF was also investigated. In accordance with our results, most of the studies found significantly higher MPV values in FMF patients and stated that FMF is associated with increased risk of atherosclerosis [6,9,10]. MPV values were found higher even in attack-free FMF cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Usefulness of MPV in assessment of atherosclerotic risk in cases with FMF was also investigated. In accordance with our results, most of the studies found significantly higher MPV values in FMF patients and stated that FMF is associated with increased risk of atherosclerosis [6,9,10]. MPV values were found higher even in attack-free FMF cases.…”
Section: Discussionsupporting
confidence: 92%
“…Mean platelet volume (MPV) and epicardial adipose tissue (EAT) thickness are novel parameters used in prediction of the risk of atherosclerosis [3,6-8]. Albeit contradictory results have been reported, there are some studies investigating the usefulness of MPV in assessment of atherosclerotic risk in cases with FMF [6,9,10]. However, no study evaluating EAT thicknesses of FMF patients was reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of clinical and subclinical inflammation are unclear during FMF attack and in the attack-free period. As in other clinical entities accompanied by inflammation, FMF patients are at an increased risk of atherosclerosis development [6,12,13]. …”
Section: Discussionmentioning
confidence: 99%
“…22,23 Moreover, NLR and MPV had higher levels at the attack periods in familial Mediterranean fever patients. 24,25 High levels of MPV and NLR have been found as a predictor for gastrointestinal bleeding in the Henoch-Schonlein purpura. 26,27 Decreased MPV and NLR have been shown with the treatment of rheumatoid arthritis and ankylosing spondylitis.…”
Section: Discussionmentioning
confidence: 99%